Chalcogenideth in Films with Micro Transitions - Naymanboyev Raxmonali; Yuldashev Abror Abduvositovich; Yuldashev Shohjahon Abrorovich; Yuldasheva Shahrizoda Abrorjon qizi (Research Parks Publishers, 2021)
This paper presents the results of studies of thin films of chalcogenides with in homogeneities of the microp-n-transition type. The current-voltage dependence (I (V)) is obtained and the analysis is carried out in some special cases. Super linear and super linear regions of the I (V) dependence are found. It is shown that the super linear region of the dependence means that the recombination losses of the injection current in the pandn-regions make up a small fraction of the saturation current of a single transition. The linear region of the I (V) dependence at the origin of coordinates depends on the degree of shunting of microjunctions.